REPRODUCTIVE ASPECTS OF THE TROPICAL ABALONE, HALIOTIS ASININA, FROM SOUTHERN LOMBOK WATERS, INDONESIA - Setyono, Dwi E.D. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2006)
The main objective of this study was to determine reproductive strategy including major spawning season of tropical abalone (Haliotis asinina) from southern Lombok waters, Indonesia. Gonad bulk index, maturity stages and oocyte size frequency distribution were applied to document gonadal development and major spawning season. The results of this study show that H. asinina in southern Lombok waters displayed year-round spawning with a high proportion occurring in August - November, when gonad index dropped to a lower level and high proportion of partly spawned and/or spent ovaries occurred in the population. Gonad development and spawning in males and females occurred synchronously. The correlation between gonadal development and environmental factors are described and discussed.